(untitled) (International journal of medical sciences, 2026)
Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder with a complex and multifactorial pathogenesis involving genetic susceptibility and neurovegetative dysregulation. This annotation focuses on the role of genetic and autonomic nervous system markers in the development of IBS, with particular attention to clinical–phenotypic stratification and prevention among military personnel. Genetic polymorphisms affecting neurotransmitter regulation, immune response, and stress reactivity contribute to individual variability in symptom severity and disease course. Neurovegetative imbalance, characterized by altered sympathetic–parasympathetic regulation, plays a key role in gut–brain axis dysfunction and stress-induced symptom exacerbation. Military personnel represent a high-risk group due to chronic psycho-emotional stress, irregular lifestyle, and increased physical demands. Identification of genetic and neurovegetative markers enables early risk assessment, targeted prevention, and personalized management strategies. Preventive approaches emphasizing stress modulation, autonomic regulation, lifestyle optimization, and early psychosomatic support are aligned with modern preventive medicine principles promoted by the World Health Organization. Integrating biomarker-based stratification into military healthcare systems may reduce IBS prevalence, improve quality of life, and enhance operational readiness.